Examining the psychometric properties of the Smartphone Addiction Scale and its short version for use with emerging adults in the U.S - Bethany Harris (Elsevier, 2020)
The Smartphone Addiction Scale (SAS) and Smartphone Addiction Scale – Short Version (SAS-SV) were originally developed and validated for use with South Korean adults and adolescents respectively. Despite being frequently used in U.S. adult populations, neither scale has been validated for this purpose. This study seeks to validate both the SAS and SAS-SV for use with U.S. emerging adults. College students ranging in age from 18 to 24 (Mage = 19.2, SD ​= 1.2, 67.3% female, N ​= ​150) completed the SAS, a modified Internet Addiction Test (IAT), the Smartphone Application-Based Addiction Scale (SABAS), the Smartphone Addiction Inventory (SPAI), and a questionnaire adapted from proposed diagnostic criteria for smartphone addiction. Results indicate high internal consistency and concurrent validity of the SAS (Cronbach’s alpha ​= ​0.93) and SAS-SV (Cronbach’s alpha ​= ​0.84). The six-factor structure of the SAS was not well-replicated and the reliability of the other potential factor structures that emerged appear questionable, suggesting that interpretation in U.S. samples may be better suited at the full scale rather than subscale level. The SAS-SV demonstrated near-equivalent predictive validity and comparable concurrent validity as compared to the SAS, suggesting that the SAS-SV offers a viable and convenient alternative to the SAS.